A Gold(I)‐Catalyzed Domino Coupling of Alcohols with Allenes Enables the Synthesis of Highly Substituted Indenes. Issue 41 (6th September 2016) - Preinfalk, Alexander; Misale, Antonio; Maulide, Nuno
Abstract: The reaction of aryl‐substituted allenes with alcohols under gold catalysis led to highly substituted indenes in good yields, with low catalyst loading and under mild conditions. During this domino transformation, two C−C bonds are formed with water as the only byproduct. Abstract : Highly substituted indenes were obtained in good yields, with low catalyst loading and under mild conditions from the reaction of aryl‐substituted allenes with alcohols under gold catalysis. During this domino transformation, two C−C bonds are formed with water as the only byproduct.